The Market Evaluation of Human Capital: The Case of Indentured Servitude - Galenson, David W. (Journal of Political Economy, 1981)
This paper examines the market for human capital created by the institution of indentured servitude in colonial America. The indenture system allowed English emigrants to obtain passage to the colonies by selling claims on their future labor. With the size of the debt approximately equal for all emigrants, the length of the term for which a servant was bound is predicted to have varied inversely with expected productivity in the colonies. Analysis of two collections of contracts made in the seventeenth and eighteenth centuries supports the prediction. Age, skill, and literacy were negatively related to length of indenture. Women received shorter terms than men at young ages, while servants bound for the West Indies and those bound in periods of high colonial demand for labor also received reductions.